บทบาท หน้าที่ความรับผิดชอบของเจ้าหน้าที่ความปลอดภัยในการทำงานกับการป้องกันผลกระทบต่อสุขภาพจากตัวทำละลายอินทรีย์ในอุตสาหกรรมฟอกหนังและผลิตเครื่องหนัง - กิตติ โพธิ์เย็น (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The overall objective of this descriptive study was to examine the role and responsibility of safety officers and their associated factors in the prevention of health impact from workplace organic solvents exposure in tanning and leather products manufacturing industry. Data were collected by mail questionnaires during August, 2001-February, 2002 from safety officers in 225 tanning and leather products enterprises throughout the country. The response rate was 60.8 percent (137 safety officers had answered the questionnaires) The results showed that the most frequent preventive practices of the safety officers were policy and chemical safety management (81.3 percent) and the least frequent practice was workers’ training and education (75.3 percent). Factors which were statistical significantly associated with the frequencies of preventive practices included qualification of safety officer, number of safety officers in the enterprise, safety officer’s previous training about chemical safety, safety officer s attached sector within the enterprise, being a member in the safety committee, type of the enterprise, ISO accreditation status of the enterprise, and the safety officer’s awareness of use and names of organic solvents in the enterprise. In conclusion, this finding indicates that safety officers should receive continual training about chemical safety, for the more effective and sustainable prevention of health hazards of organic solvents exposure in the tanning and leather products manufacturing industry.